Proper collimation effect on radiation dose and image quality in thoracic spine radiography - Pazanin Anamaria; Skrk Damijan; Zalokar Nika; Mekis Nejc (Nuclear Technology and Radiation Protection, 2020)
The purpose of this research was to determine the impact of collimation in thoracic spine radiography on patient exposure and image quality. The study was performed on 84 patients referred to thoracic spine radiography. Patients were randomly divided into two equal groups of 42. The first group was imaged according to the standard collimation protocol used in one of the hospitals in Croatia while the second group was imaged by applying “optimal” collimation, image field size was individually collimated for each patient or according to the greatest image field collimation depicted in professional literature. For each patient body mass index, image field size, exposure conditions and dose area product were noted and absorbed doses by organs were calculated, image quality was assessed. There were no statistically significant differences in BMI between the two groups of patients. With the optimal collimation the size of the imaging field in the anteroposterior projection was reduced by 45 % ( p < 0.001) and in the lateral projection by 41 % (p < 0.001). The study also showed reduced values of DAP for anteroposterior projection by 34 % ( p = 0.007) and for lateral projection by 23 % ( p = 0.040). The mean absorbed dose to the selected organs decreased by 26 % in the anteroposterior projection and by 28 % in the lateral projection. In addition, the optimal collimation protocol improved image quality by 13 % in anteroposterior projection. No differences in image quality were found in lateral projection. By carrying out this research we have demonstrated that optimal collimation in thoracic spine imaging has a strong influence on patient exposure to radiation and has a positive impact on image quality.